PENERAPAN SSDE-DIAMETER EKUIVALEN AIR SEBAGAI TINGKAT PANDUAN DIAGNOSIS TYPICAL VALUE PADA PEMERIKSAAN CT SCAN ABDOMEN PEDIATRIK - Ni Larasati Kartika Sari; Rahayugo Rahayugo; Budi Santoso; Puji Hartoyo (JURNAL PEMBELAJARAN FISIKA, 2023)
Diagnostic Reference Level (DRL) is a method of optimizing patient doses in diagnostic and intervention procedures. The DRL value is obtained from the Volumetric Computed Tomography Dose Index (CTDIvol) which is obtained from a phantom with a diameter of 16 cm or 32 cm, so it is not yet possible to accurately estimate the dose for each patient, especially pediatric patients. The American Association of Physicists in Medicine (AAPM) then issued a water equivalent diameter (Dw) parameter to calibrate the CTDIvol to obtain a Size-Specific Dose Estimate (SSDE) so that it is more specific and effective. This study aims to obtain local DRL values ​​and compare local DRL values ​​in two pediatric age groups. This study used data from 25 pediatric abdominal CT scan patients aged <15 years, divided into two groups, ages 0-4 years and ages 5-15 years. The results of this study showed that typical DRLCTDIvol values ​​for ages 0-4 years and 5-15 years were 3.09 mGy and 4.39 mGy respectively, while DRLSSDE for the two age groups were 3.25 mGy and 3.54 mGy respectively. There is a difference of 5.27% and 19.36% respectively from the local DRL value based on CTDIvol and SSDE for the two age groups. It can be seen that in the 0-4 year age group, the DRLSSDE value is greater than the DRLCTDIvol, conversely in the 5-15 year age group the DRLSSDE value is lower than the DRLCTDIvol which indicates that the dimensional factor affects the dose received by the patient.